EuroHYP‐1: European multicenter, randomized, phase III clinical trial of therapeutic hypothermia plus best medical treatment vs. best medical treatment alone for acute ischemic stroke. Issue 5 (15th May 2014) - van der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Demotes, Jacques; Durand‐Zaleski, Isabelle; Gebhardt, Bernd; Gluud, Christian; Kollmar, Rainer; Krieger, Derk W.; Lees, Kennedy R.; Molina, Carlos; Montaner, Joan; et al.
<x xml:space="preserve">Abstract</x> Rationale Cooling reduced infarct size and improved neurological outcomes in animal studies modeling ischemic stroke, and also improved outcome in randomized clinical trials in patients with hypoxic‐ischemic brain injury after cardiac arrest. Cooling awake patients with ischemic stroke has been shown feasible in phase II clinical trials. Primary aim To determine whether systemic cooling to a target body temperature between 34·0 and 35·0°C, started within six‐hours of symptom onset and maintained for 24 h, improves functional outcome at three‐months in patients with acute ischemic stroke. Design International, multicenter, phase III, randomized, open‐label clinical trial with blinded outcome assessment in 1500 patients aged 18 years or older with acute ischemic stroke and a National Institutes of Health Stroke Scale score of 6 up to and including 18. In patients randomized to hypothermia, cooling to a target body temperature of 34–35°C will be started within six‐hours after symptom onset with rapid intravenous infusion of refrigerated normal saline or a surface cooling technique and maintained for 24 h with a surface or endovascular technique. Patients randomized to hypothermia will receive pethidine and buspirone to prevent shivering and discomfort. Primary outcome Score on the modified Rankin Scale at 91 days, as analyzed with ordinal logistic regression and expressed as a common odds ratio. Discussion With 750 patients per intervention group, this trial has 90% power to detect 7% absolute improvement at the 5% significance level. The full trial protocol is available at http://www.eurohyp1.eu. ClinicalTrials.gov Identifier: NCT01833312.